2021
DOI: 10.1002/jdd.12732
|View full text |Cite
|
Sign up to set email alerts
|

Exploring mindfulness and artworks/drawings to predict dental students’ performance

Abstract: Purpose/Objectives: To explore and assess self-reported trait mindfulness and artwork/drawings as tools to predict students' performance.Methods: This longitudinal study explored whether year 2 dental students' artwork/drawings produced during the first week of a preclinical endodontics course and Mindfulness Attention Awareness Scale (MAAS) scores could be used as a predictor of performance (grades/rank) at the end of the course. A convergent design of mixed methods approaches was used to integrate the quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 44 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…One study found no correlation between a typodont preparation examination, designed to provide a measure of students’ clinical skills, and a clinical competency exam involving the preparation of a full crown in a patient [ 33 ]. In addition, some of our previous qualitative findings have found that dental students were skeptical of the usefulness of learning procedures on mannequins/typodonts and how this experience would translate to making them proficient enough to provide dental care for a real person [ 23 ]. The traditional dental education context consists of very different preclinical and clinical conditions, in which students acquire various skills sets necessary to be successful [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One study found no correlation between a typodont preparation examination, designed to provide a measure of students’ clinical skills, and a clinical competency exam involving the preparation of a full crown in a patient [ 33 ]. In addition, some of our previous qualitative findings have found that dental students were skeptical of the usefulness of learning procedures on mannequins/typodonts and how this experience would translate to making them proficient enough to provide dental care for a real person [ 23 ]. The traditional dental education context consists of very different preclinical and clinical conditions, in which students acquire various skills sets necessary to be successful [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two researchers independently analyzed the 15 artworks (students n = 9 and faculty members n = 6). Each artwork was analyzed in terms of what characteristics were elicited in the images (such as: positive or negative feelings/emotions, colors, and sizes) [ 23 , 24 ]. For this purpose, emotions were defined not only as face or body expressions (physical dimension of the definition), but also as psychological dimensions in reaction to the outside world ( i.e ., expressing what is occurring inside the body to the outside world) [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations